Computational investigation and passive control of vehicle sunroof buffeting. (15th November 2019) - He, Yansong; Zhang, Quanzhou; An, Changfa; Wang, Yong; Xu, Zhongming; Zhang, Zhifei
A computational fluid dynamics simulation method based on large eddy simulation is presented and applied to compute the sunroof buffeting of a sport utility vehicle. The simulation result, i.e. the buffeting level curve, coincides well with the road test. The simulation method is then employed to investigate the sunroof buffeting of a vehicle during the development process in the range of 30 km/h–90 km/h. The results show that the most severe sunroof buffeting occurs at 70 km/h, which corresponds to the resonant frequency of the cabin. Flow field visualizations reveal that strong pressure fluctuations are generated inside the cabin due to vortex shedding from the leading edge and impinging onto the trailing edge of the sunroof opening, which explains the mechanism of sunroof buffeting. A new deflector with a gap and a notched upper edge is designed to replace the original castle type deflector. The simulation results show that the newly designed deflector can reduce the buffeting level to 97.9 dB; that is, the sunroof buffeting is completely eliminated. Moreover, the phenomenon of sunroof buffeting reduction is explained by comparing and analyzing the flow field between the newly designed deflector and the original deflector.